1993
DOI: 10.1038/bjc.1993.470
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary cancer after Hodgkin's disease in patients in the British National Lymphoma Investigation: relationships to host factors, histology and stage of Hodgkin's disease, and splenectomy

Abstract: Summary The risks of second primary cancer were analysed in 2846 patients with Hodgkin's disease treated within the British National Lymphoma Investigation during 1970-87. The relative risk (RR) of leukaemia was significantly greater in women (RR = 30.1; 95% confidence limits (CL) 13.0-59.5) than in men (RR = 10.9; 95% CL 4.7-21.5), and showed a significant trend of greater risk with younger age at first treatment (P<0.001). The relative risk of solid cancers was similar between the sexes, but again significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 17 publications
4
17
1
4
Order By: Relevance
“…The decrease in relative risk of second cancers overall with increasing age at first treatment accords with several previous reports (Glicksman et al, 1982;Sont et al, 1992;Abrahamsen et al, 1993;Swerdlow et al, 1993). For leukaemia, previous studies (Glicksman et al, 1982;van der Velden et al, 1988;Abrahamsen et al, 1993;Swerdlow et al, 1993) agree with the present analyses that relative risks diminish beyond middle age, and this has been the case in analyses where ANLL or AML were analysed separately (Glicksman et al, 1982;van der Velden et al, 1988), but results have been variable with regard to the trend in risks at younger ages of first treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The decrease in relative risk of second cancers overall with increasing age at first treatment accords with several previous reports (Glicksman et al, 1982;Sont et al, 1992;Abrahamsen et al, 1993;Swerdlow et al, 1993). For leukaemia, previous studies (Glicksman et al, 1982;van der Velden et al, 1988;Abrahamsen et al, 1993;Swerdlow et al, 1993) agree with the present analyses that relative risks diminish beyond middle age, and this has been the case in analyses where ANLL or AML were analysed separately (Glicksman et al, 1982;van der Velden et al, 1988), but results have been variable with regard to the trend in risks at younger ages of first treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Careful clinical surveillance to detect breast cancers early is needed in women treated young with mantle radiotherapy. The only previous data on relative risks by age at first treatment for solid cancers more generally appear to be those from the BNLI (Swerdlow et al, 1993), which showed a significant trend of increasing relative risk with decreasing age (although less steep than in the present study) for non-lung solid cancers, and a nonsignificant trend in the same direction (except that no cases occurred under age 25) for lung cancer. The sole previous analyses by attained age appear to be those on breast cancer risk by Hancock et al (1993).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Although the AR increased with age, because malignancy is more common with increasing age, the relative risk of developing a second malignancy was greater in younger patients in this study, as has been reported by others (Henry-Amar, 1992;Swerdlow et al, 1992). Splenectomy has been reported as a risk factor for second malignancy in some studies (van Leeuwen et al, 1994) but not others (Valagussa et al, 1986;Swerdlow et al, 1993). The IDHD reported a relative risk of 1.3 for development of acute leukaemia (P < 0.05) and 1.4 for non-Hodgkin's lymphoma (P < 0.1).…”
Section: Male Fertilitysupporting
confidence: 76%
“…Most of these studies have not included patients with uniform diagnoses and comparisons with similar patients not receiving high-dose therapy have not been made. This latter point is of great importance as secondary leukaemia is a well documented complication of standard dose chemotherapy for lymphoma, especially Hodgkin's disease (Tucker et al, 1988;Devereux et al, 1990;Swerdlow et al, 1993). A number of risk factors have been identified in the literature.…”
mentioning
confidence: 99%